PENERAPAN MULTIMEDIA SITUS LANGUAGES ONLINE DALAM PEMBELAJARAN KETERAMPILAN BERBICARA BAHASA PRANCIS - Elsa Gisella, - (2019)
This study aims to describe the application of multimedia "Language Online site: French" in learning French speaking skills. The actual result is multimedia can stimulate learners to remember the contents of the lesson faster through visual media followed with text. The multimedia benefit for educator is the effectiveness of time by guiding each learner as a whole and simultaneously. In addition, the educator applied a learning by doing method to all learners. The suggestion from the result of this study that the educator to use multimedia suite with the learners abilities.----------Cette étude a pour objectif de décrire l'application du multimédia «Site Web Language Online: French» dans l'apprentissage de Production Orale. Le résultat montre que le multimédia peut inciter les apprenants à mémoriser plus rapidement le contenu de la leçon par le biais de supports visuels suivis de texte. L'avantage du multimédia pour l'enseignant est l'efficacité du temps en guidant chaque apprenant simultanément. En outre, l'enseignant a appliqué une méthode d'apprentissage par la pratique à tous les apprenants que l'enseignant utilise d'oufres multimédias selon les capacités des apprenants.